Limbic encephalitis associated with anti-NH(2)-terminal of α-enolase antibodies: A clinical subtype of Hashimoto encephalopathy - Kishitani, Toru (Medicine (Baltimore), 2017)
Several types of autoantibodies have been reported in autoimmune limbic encephalitis (LE), such as antibodies against the voltage-gated potassium channel (VGKC) complex including leucine-rich glioma inactivated 1 (LGI1). We recently reported a patient with autoimmune LE and serum anti-NH(2)-terminal of α-enolase (NAE) antibodies, a specific diagnostic marker for Hashimoto encephalopathy (HE), who was diagnosed with HE based on the presence of antithyroid antibodies and responsiveness to immunotherapy. This case suggests that LE patients with antibodies to both the thyroid and NAE could be diagnosed with HE and respond to immunotherapy. The aim of this study was to clarify the clinicoimmunological features and efficacy of immunotherapy in LE associated with anti-NAE antibodies to determine whether the LE is a clinical subtype of HE. We examined serum anti-NAE antibodies in 78 LE patients with limbic abnormality on magnetic resonance imaging and suspected HE based on positivity for antithyroid antibodies. Nineteen of the 78 patients had anti-NAE antibodies; however, 5 were excluded because they were double positive for antibodies to the VGKC complex including LGI1. No antibodies against the N-methyl-D-aspartate receptor (NMDAR), contactin-associated protein 2 (Caspr2), γ-aminobutyric acid-B receptor (GABA(B)R), or α-amino-3-hydroxy-5-methylisoxazole-4-propionic acid receptor (AMPAR) were detected in the 19 patients. Among the remaining 14 who were positive only for anti-NAE antibodies, the median age was 62.5 (20–83) years, 9 (64%) were women, and 8 (57%) showed acute onset, with less than 2 weeks between onset and admission. Consciousness disturbance (71%) and memory disturbance (64%) were frequently observed, followed by psychiatric symptoms (50%) and seizures (43%). The frequency of these symptoms significantly differed between the acute- and subacute-onset groups. Abnormalities in cerebrospinal fluid and electroencephalogram were commonly observed (92% for both). Tumors were not identified in any cases. All patients responded to immunotherapy or spontaneously remitted, thereby fulfilling the criteria of HE. This study demonstrated that LE associated with anti-NAE antibodies is a nonparaneoplastic LE and various limbic symptoms that depend on the onset type. Favorable therapeutic efficacy suggests that this LE can be considered a clinical subtype of HE and that anti-NAE antibodies may be a promising indicator of the need for immunotherapy.